2014
DOI: 10.1007/s00432-014-1729-9
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor promoter methylation predicts survival in low-grade ovarian carcinoma patients

Abstract: Although small numbers of ovarian carcinoma patients were analyzed, methylation status might be useful as a prognostic marker within the subgroup of low-grade ovarian carcinoma patients. Further studies should investigate a larger cohort and also address the use of demethylation agents with respect to improve patient's prognosis in this subgroup of ovarian carcinoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Numerous studies have aimed to introduce new biological prognostic factors in ovarian cancer. Recently, carbohydrate stem cell marker TF1 has been proposed as negative prognostic marker in ovarian cancer displaying wildtype p53, while estrogen receptor promoter methylation could predict overall survival in low-grade ovarian carcinoma patients [5,6]. Although for these and various other molecules the prognostic value independently of clinical parameters has been proven, until today, except for breast cancer gene (BRCA)-status, no biological marker is commonly accepted [4].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have aimed to introduce new biological prognostic factors in ovarian cancer. Recently, carbohydrate stem cell marker TF1 has been proposed as negative prognostic marker in ovarian cancer displaying wildtype p53, while estrogen receptor promoter methylation could predict overall survival in low-grade ovarian carcinoma patients [5,6]. Although for these and various other molecules the prognostic value independently of clinical parameters has been proven, until today, except for breast cancer gene (BRCA)-status, no biological marker is commonly accepted [4].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that PTEN, as a key link, is involved in the PI3K/AKT/PTEN drug-resistance pathway and participates in drug resistance in OC by affecting biological processes, such as DNA methylation, cell cycle, apoptosis, and cell proliferation. [ 11 , 20 22 ] In addition, it had been reported that changes in gene methylation of ESR1 [ 23 , 24 ] are involved in the development and drug resistance in OC and are associated with prognosis. With reference to MDM2 and CD44, although no previous studies have shown that changes in methylation are associated with OC and drug resistance in OC, numerous studies have indicated that both MDM2 and CD44 genes are involved in drug resistance in OC, and are related to the prognosis of OC.…”
Section: Resultsmentioning
confidence: 99%
“…[ 38 ] However, some studies have also shown that in low-grade serous ovarian cancer, the degree of methylation of the ESR1 promoter is negatively related to survival rate. [ 24 ] Another example is that ETS1 is a key regulator of the PARP1 gene in BRCA1 mutant ovarian cancer, and its degree of methylation is significantly associated with the prognosis of OC. [ 14 ] In addition, CD44-positive cells of OC are associated with poor prognosis of OC.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that loss of ESR in breast cancer patients indicates invasiveness and poor prognosis 28. In ovarian carcinoma, ESR1 methylation influences ovarian cancer development, and its promoter methylation was negatively correlated with survival in the subgroup of low-grade ovarian carcinoma patients 29…”
Section: Discussionmentioning
confidence: 99%